THU0397 Increased Bone Mass and Bone Strength by Sclerostin Antibody (Scl-Ab) is Maintained by a RANKL Inhibitor in OVX Rats with Established Osteopenia. (23rd January 2014) - Ominsky, M.; Li, X.; Warmington, K.; Niu, Q.-T.; Asuncion, F.; Dwyer, D.; Grisanti, M.; Han, C.-Y.; Kostenuik, P.; Stolina, M.; Ke, H.
Abstract : Background: Some Scl-Ab-induced BMD gains gradually reversed after treatment discontinuation in rats. Objectives: To examine if follow-up treatment with a RANKL inhibitor, OPG-Fc, would maintain Scl-Ab-induced bone mass gains in OVX rats. Methods: Six-month-old OVX rats (2 months post-OVX) were treated with Scl-Ab (Scl-Ab VI, 25 mg/kg, SC, 1x/wk) for 6 wks and then transitioned to vehicle (Veh) or OPG-Fc (10 mg/kg, SC, 2x/wk) for another 6 or 20 wks (n=12-14/group). Veh-treated Sham and OVX control rats were euthanized at wks 0, 6, 12, and 26, and a group of Scl-Ab-treated OVX rats were euthanized at wk 6 (n=10-12/group). Results: In vivo DXA analysis showed that after 6 wks, Scl-Ab-treated OVX rats increased lumbar spine and femur-tibia BMD to levels significantly above OVX and Sham controls. These treatment-related increases were maintained by transition to OPG-Fc, and gradually reversed by transition to Veh (Fig.). Histomorphometry revealed significant increases in vertebral trabecular bone volume (BV/TV) and tibial cortical thickness (Ct.Th) after 6 wks of Scl-Ab treatment. While transition to OPG-Fc maintained BV/TV and Ct.Th at the peak levels achieved with Scl-Ab, transition to Veh led to gradual declines in these parameters to levels that remained above OVX controls at wk 26. Significant increases in trabecular, endocortical, and periosteal bone formation rates and significant decreases in trabecular and endocortical eroded surfaces were also associated with Scl-Ab treatment (6 wks). Transition to OPG-Fc led to reductions in each of these bone resorption and formation parameters, however transition to Veh reversed these changes. At wk 26, maximum load of lumbar vertebral bodies was significantly greater in the OPG-Fc vs Veh transitioned group. Conclusions: After discontinuing Scl-Ab treatment, transitioning to the RANKL inhibitor OPG-Fc effectively inhibited bone resorption and maintained Scl-Ab-induced bone mass and bone strength gains. Disclosure of Interest: M. Ominsky Shareholder of: Amgen Inc., Employee of: Amgen Inc., X. Li Shareholder of: Amgen Inc., Employee of: Amgen Inc., K. Warmington Shareholder of: Amgen Inc., Employee of: Amgen Inc., Q.-T. Niu Shareholder of: Amgen Inc., Employee of: Amgen Inc., F. Asuncion Shareholder of: Amgen Inc., Employee of: Amgen Inc., D. Dwyer Shareholder of: Amgen Inc., Employee of: Amgen Inc., M. Grisanti Shareholder of: Amgen Inc., Employee of: Amgen Inc., C.-Y. Han Shareholder of: Amgen Inc., Employee of: Amgen Inc., P. Kostenuik Shareholder of: Amgen Inc., Employee of: Amgen Inc., M. Stolina Shareholder of: Amgen Inc., Employee of: Amgen Inc., H. Ke Shareholder of: Amgen Inc., Employee of: Amgen Inc.